Pertumbuhan Miselium Bibit F1 Jamur Tiram Putih dan Jamur Merang pada Media Kardus dan Arang Sekam Dengan Bekatul sebagai Campuran Media - Rahayu, Bety; , Suparti, M.Si (2016)
Seed is an important factor for determining the quality of growth and productivity mushrooms. Mycelium growth F1 seed oyster mushroom and straw mushroom mycelium characterized by the appearance on the surface of the media. Seed oyster mushrooms and straw mushroom which is well marked by growing mycelium evenly on the surface and white media. This study aims to determine the growth of oyster mushroom mycelium and straw mushroom using cardboard media and rice husk with the addition of rice bran on the medium to long mycelium. This study uses a completely randomized design with two factors: the type of media and the type of fungus. Parameters measured were mycelium growth (cm). The results were analyzed with a qualitative description method. The results showed that the growth of the mycelium on cardboard highest media with this type of oyster mushroom is 7.0 cm and a low with this type of straw mushroom that is 5.9 cm. While the rice husk highest on the type of oyster mushroom of 4.2 cm and a low on the type of straw mushroom that is 4.1 cm. , It can be concluded that the media box and rice husk can be used as a medium for mycelium growth F1 seed oyster mushroom and straw mushroom. Media cardboard has the best mycelial growth compared to rice husk